2011
DOI: 10.1177/0952076710380766
|View full text |Cite
|
Sign up to set email alerts
|

Public service bargains in Dutch top civil service

Abstract: In this article the position, role and functioning of the highest ranking officials in the Dutch civil service is discussed, using the theory of public service bargains (PSBs) as outlined by Hood and Lodge (2006). For the notion of a shift in PSB to be studied, we need a clear view on the initial PSB. We therefore first describe Dutch society and politics and the type of bargain traditionally found in Dutch public service, and briefly consider the reforms which might have had an impact on the PSB. Next, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 7 publications
0
27
1
6
Order By: Relevance
“…Beyond the foundation supplied by Hood and Lodge (2006), these ideas have received fairly limited testing . Ideal‐type PSB categories have been found rare in practice, with overlap and hybridization common (Bourgault and Van Dorpe ; Steen and Van der Meer ). The terms of PSBs can also be ambiguous, which can be used strategically by bargaining actors (Burns, Wei, and Peters ).…”
Section: Public Service Bargainsmentioning
confidence: 99%
“…Beyond the foundation supplied by Hood and Lodge (2006), these ideas have received fairly limited testing . Ideal‐type PSB categories have been found rare in practice, with overlap and hybridization common (Bourgault and Van Dorpe ; Steen and Van der Meer ). The terms of PSBs can also be ambiguous, which can be used strategically by bargaining actors (Burns, Wei, and Peters ).…”
Section: Public Service Bargainsmentioning
confidence: 99%
“…Other publications based on the same research have shown that the initial PSB, which was in place before the public management reform movement in each country, still has an important impact on the current PSB (Bourgault, 2011;de Visscher et al, 2011a;Hansen and Salomonsen, 2011;Steen and Van der Meer, 2011;Van Dorpe and Horton, 2011).…”
Section: Conclusion: How Strong Is the Managerial Psb?mentioning
confidence: 94%
“…Following Hood and Lodge's account of shifts in PSBs in the UK and Germany, the concept has recently been tested in Belgian, Canadian, Danish, Dutch, New Zealand and UK state administration (Bourgault, 2011;De Visscher et al, 2011;Hansen and Salomonsen, 2011;Lodge and Gill, 2011;Steen and van der Meer, 2011;Van Dorpe and Horton, 2011). This research provided a moderate picture.…”
Section: The Public Service Bargain Of the Top Civil Servantsmentioning
confidence: 99%
“…The performance agreements lack a clear managerial spirit because of their soft nature and lack of harsh consequences in case of disappointing results. As a result, characteristics of a traditional reward system -such as elements of permanence, career progression and generous pay -persist alongside the new managerial traits (Steen and van der Meer, 2011). The responsibilities that Secretaries-General have are quite demanding since they are in charge of leading all ministerial tasks and responsibilities.…”
Section: The Public Service Bargain Of the Top Civil Servantsmentioning
confidence: 99%
See 1 more Smart Citation